2019
DOI: 10.15420/cfr.2018.27.2
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Routine Heart Failure Clinical Care

Abstract: Heart failure is a clinical condition with complex pathophysiology that involves many different processes. Diagnosis is often difficult in patients presenting for the first time with breathlessness. Many biomarkers have been identified that are elevated in heart failure and their role in assessing prognosis has also been investigated. However, at present the natriuretic peptides appear to be the gold standard biomarker against which the other biomarkers are compared. In this review we will examine the evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 74 publications
1
81
0
8
Order By: Relevance
“…Studies have shown elevation of cardiac injury markers and acute phase proteins are indicators of cardiovascular events associated with influenza virus infection (38,39). Myocardial injury can be determined by serum biomarkers including the MB form of creatine kinase (CK-MB), lactate dehydrogenase (LDH), and troponin (TnT) (40,41). Cardiac injury markers are shown to be elevated in influenza-positive veterans within 30 days of laboratory confirmation (42).…”
Section: Association Between Influenza Virus Infection and Cardiovascmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown elevation of cardiac injury markers and acute phase proteins are indicators of cardiovascular events associated with influenza virus infection (38,39). Myocardial injury can be determined by serum biomarkers including the MB form of creatine kinase (CK-MB), lactate dehydrogenase (LDH), and troponin (TnT) (40,41). Cardiac injury markers are shown to be elevated in influenza-positive veterans within 30 days of laboratory confirmation (42).…”
Section: Association Between Influenza Virus Infection and Cardiovascmentioning
confidence: 99%
“…Acute phase proteins are also potential biomarkers for cardiovascular diseases. B-type natriuretic peptide (BNP) and N-terminal proBNP (NT-proBNP) are the biomarkers in diagnosis of heart failure (40,41). Increased levels of C-reactive protein (CRP) and NT-proBNP, along with increased leukocyte numbers, correlated with mortality rate in elderly patients with 2009 H1N1 infections and cardiovascular diseases (43).…”
Section: Association Between Influenza Virus Infection and Cardiovascmentioning
confidence: 99%
“…[3][4][5][6] Nevertheless, with the growing complexity and heterogeneity observed in HF progression, delineation of more reliable biomarkers with higher specificity and sensitivity for the early diagnosis and molecular monitoring of the disease state, and for having an accurate expectation of prognosis with sufficiently predictive precision is still urgent to optimize treatment options and decline mortality. 7 Besides high sensitivity and specificity, the ideal and implementable biomarker must meet several key criteria. It needs to be readily accessible; a biomarker must be ideally detected in easily reachable body fluids, such as plasma/serum, saliva, and urine.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of studying cardiac biomarkers in the diagnosis and prognostic stratification of children with HF has been well emphasized; these biomarkers may act as future therapeutic targets (7). Similarly, noninvasive tools to monitor patients with HF before the occurrence of clinical deterioration are also required (8).…”
Section: Introductionmentioning
confidence: 99%